1988
DOI: 10.1016/0035-9203(88)90524-x
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis in Sierra Leone 2: a comparison of forest and savanna villages

Abstract: Very little of the original primary forest remains in Sierra Leone and the savanna is mainly woodland or a forest-savanna mosaic. The prevalence of microfilariae of Onchocerca volvulus, nodules and moderate or severe skin lesions was higher in forest than savanna villages. In forest villages the prevalence of microfilariae was 71.8% at the iliac crest, 36.6% (outer canthus), 12.8% (cornea) and 34.1% in the anterior chamber of the eye. Corresponding figures for the savanna villages were 51.9%, 20.5%, 5.6% and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Male preponderance is consistent with other observations in Ethiopia (1,(5)(6)(7) and elsewhere (19,20).…”
Section: Discussionsupporting
confidence: 92%
“…Male preponderance is consistent with other observations in Ethiopia (1,(5)(6)(7) and elsewhere (19,20).…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that the regional and district variations of onchocerciasis prevalence at baseline could be linked with vector ecology and density, which also depend on the distance of villages studied from the river basin and the geography of the river [ 39 ]. Previous studies in Sierra Leone showed that O. volvulus MF prevalence was higher in the forest (71.8%) than in Savannah villages (51.9%) [ 30 ]. In general, the eastern region has the forest strain of the O. volvulus parasite, characterised by low intensity of infection, mild skin disease and relatively low blindness rate; the southern region has a mixture of forest and Savannah strains of the parasite, characterised by high infection intensity, mild skin disease and relatively higher blindness rate (sometimes higher than blindness rates recorded in the Savannah area); and the northern region has the Savannah strain of the parasite, characterised by high infection intensity, mild skin disease, and relatively high blindness rate [ 14 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that the disease is virtually ubiquitous in adults in many of the rural areas and that onchocercal blindness is present, though rarely at a prevalence higher than 2.5%. However, a few foci of severe onchocerciasis, comparable with those of hyperendemic villages in savanna West Africa, have been shown to occur in some forest areas (McMahon et al, 1988).…”
Section: Introductionmentioning
confidence: 99%